Migrant and native women's perceptions of prenatal care communication quality: the role of host-country language proficiency - Sousan Hamwi; Elsa Lorthe; Milton Severo; Henrique Barros (BMC, 2023)
Abstract Background Despite the potentially significant impact of women-prenatal care provider communication quality (WPCQ) on women's perinatal health, evidence on the determinants of those perceptions is still lacking, particularly among migrant women. Methods We aimed to examine the effect of women's host-country language proficiency on their perceived WPCQ. We analyzed the data of 1210 migrant and 1400 native women who gave birth at Portuguese public hospitals between 2017 and 2019 and participated in the baMBINO cohort study. Migrants' language proficiency was self-rated. Perceived WPCQ was measured as a composite score of 9 different aspects of self-reported communication quality and ranged from 0 (optimal) to 27. Results A high percentage of women (29%) rated communication quality as "optimal". Zero-inflated regression models were fitted to estimate the association between language proficiency and perceived WPCQ. Women with full (aIRR 1.35; 95% CI 1.22,1.50), intermediate (aIRR 1.41; 95% CI 1.23,1.61), and limited (aIRR 1.72; 95% CI 1.45,2.05) language proficiencies were increasingly more likely to have lower WPCQ when compared to natives. Conclusions Facilitating communication with migrant women experiencing language barriers in prenatal care could provide an important contribution to improving prenatal care quality and addressing potential subsequent disparities in perinatal health outcomes.